Validation of Honesty Test using Situational Judgment Test Format - Kwon, EunA; Lee, JongGoo (Korean Journal of Industrial and Organizational Psychology, 2020)
The purposes of this research were to develop the Honesty test using situation judgment test format to reduce the possibility of faking good in personality scales and to identify construct validity and concurrent validity of the developed scale. Total 359 employees(male, 46.24%; female, 53.76%) were used in this study. The Honesty test developed in this study consists of 5 to 6 items 6 items for each 4 sub-constructs (i.e., sincerity, fairness, greed avoidance and modesty) of honesty-humility factor in HEXACO model. Confirmatory factor analysis to assess the construct validity of the Honesty test resulted in favorable goodness of fit indexes for the 4-factor model(CFI = .946, TLI = .925, RMSEA = .046). Also, favorable goodness of fit indexes(CFI = .934, TLI = .911, RMSEA = .049) in the higher-order factor analysis showed that the 4 sub-constructs were converged into the single honesty-humility factor. To investigate the possibility of faking good could be reduced in the situational judgment test format compared to the Likert test format in measuring honesty, correlations between the honesty scores in each test format and the scores of faking good were compared. Although the correlations between the humility sub-constructs(i.e., greed avoidance and modesty) and faking good scores were not significantly different depending on the measurement format, the correlations between the honesty sub-constructs(i.e., sincerity and fairness) and faking good scores were significantly low in the situational judgment test format than in the Likert test format. The concurrent validity analyses revealed that the Honesty test using situational judgment test format had significant correlations with Machiavellism personality(r = -.21) and self-control(r = .27). Limitations of the study and directions for future study were discussed.